2014
DOI: 10.1111/vru.12193
|View full text |Cite
|
Sign up to set email alerts
|

Initial Influence of Right Versus Left Lateral Recumbency on the Radiographic Finding of Duodenal Gas on Subsequent Survey Ventrodorsal Projections of the Canine Abdomen

Abstract: Identification of the duodenum and potential abnormalities on survey abdominal radiographs is often difficult unless it contains gas. This study investigated the effect of patient positioning on the presence of duodenal gas in survey abdominal radiographs. One hundred dogs receiving a three-view survey abdominal radiographic study were enrolled in a prospective, randomized study where all dogs were divided into two groups. Group A (n = 51) dogs had a left lateral projection first, followed by a ventrodorsal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
8
1
Order By: Relevance
“…A gastric or intestinal ulcer is unlikely to be visible in survey radiographs but duodenal pseudoulcers may be observed in survey radiographs, particularly in dogs positioned in left lateral recumbency (Vander Hart & Berry ). These structures, which may also be identifiable in ultrasound and CT images, may be distinguished from true ulcers because they are normally multiple, evenly spaced and occur on the anti‐mesenteric border of the descending duodenum, whereas the majority of duodenal ulcers occur near the cranial duodenal flexure and pyloric canal (Stanton & Bright ).…”
Section: Discussionmentioning
confidence: 99%
“…A gastric or intestinal ulcer is unlikely to be visible in survey radiographs but duodenal pseudoulcers may be observed in survey radiographs, particularly in dogs positioned in left lateral recumbency (Vander Hart & Berry ). These structures, which may also be identifiable in ultrasound and CT images, may be distinguished from true ulcers because they are normally multiple, evenly spaced and occur on the anti‐mesenteric border of the descending duodenum, whereas the majority of duodenal ulcers occur near the cranial duodenal flexure and pyloric canal (Stanton & Bright ).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly surprising as most subjects presented here had gastrointestinal foreign material with or without mechanical ileus and a prior collection of case reports demonstrated the increased diagnostic utility of the left lateral view, in addition to the right lateral view, for a selection of similar cases . Authors of a recent study comparing the distribution of gas within the duodenum based on initial right‐ vs. left‐ lateral recumbency speculated that the new two‐view standard abdominal radiographic study could include left lateral and ventrodorsal views for cases where gastrointestinal obstruction is suspected or needs to be ruled out . Our findings would support this as it seems any previously inferred increased diagnostic accuracy for such cases is more likely related to having obtained a left lateral view at all (i.e., as part of a two‐view examination), rather than in addition to initial right lateral and ventrodorsal views.…”
Section: Discussionmentioning
confidence: 72%
“…Variability in the appearance of the stomach and particularly the pylorus with regard to laterality of the acquired images has been demonstrated . A recent publication demonstrated that the order in which radiographs are obtained also changes the typical distribution of gas within the gastrointestinal tract and hence would be implied to affect the ability to identify lesions and arrive at a correct diagnosis . Differences in the appearance of organs, such as the spleen, have also been noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence in dogs support acquiring both the right and left lateral recumbent views, making three‐view radiographic studies increasingly common . Inclusion of a left lateral view as part of the standard protocol in dogs improves visibility of the gastric outflow tract due to positioning of gas within its non‐gravity dependent lumen to allow better assessment of diameter as well as the presence of any nonmobile radiopaque luminal content such as foreign bodies to be highlighted by gas serving as negative contrast . It was additionally shown in canine patients that gas is best distributed to the pyloric antrum and duodenum when the left lateral view is obtained first .…”
Section: Introductionmentioning
confidence: 99%